How Will Indonesia's Remittance Value for The Next 5 Years Due to Covid-19? (Autoregressive Integrated Moving Average Approach) - Hasbi, M. Zidny Nafi' (El-Qish: Journal of Islamic Economics, 2022)
This study aims to explore how the value of Indonesia's remittances for the next 5 years due to the Covid-19 pandemic. Preliminary data obtained from the World Bank 1985-2020. By using the autoregressive integrated moving average approach, researchers can forecast the remittance value for the years 2021-2025. After processing the data, the forecast value of remittances for 5 consecutive years is 20.65%, 23.01%, 20.73%, 20.76%, and 2078%. The results of the study show that the value of Indonesian remittances has decreased by due to the pandemic compared to 2020, which is 22.95%. The decline was around 2.27%. This is interesting because although the number of Indonesian remittance transactions has decreased, the volume of remittances has increased. The remittances made large-scale remittances due to restrictions imposed by the government so that the remittance value remained stable when compared to 2008 which experienced a drastic decline. This achievement cannot be separated from government policies that have taken good preventive measures. However, it is hoped that from the forecast results, the government will continue to maximize its policies so that the value of Indonesia's remittances will increase rapidly and will make a large contribution to growth.